Social Determinants of Tooth Loss among a Group of Iranian Female Heads of Household - Taraneh Movahhed; Behjatalmolook Ajami; Mojtaba Dorri; Nima Biouki; Hadi Ghasemi; Mohammad Taghi Shakeri; Mahboobe Dehghani (Journal of Dental Research, Dental Clinics, Dental Prospects, 2015)
Background and aims. Tooth loss may lead to mastication disability, which in turn has important impact on individual’s quality of life. Social and psychological factors have been shown to be associated with tooth loss. This study aimed to in-vestigate the social determinants and prevalence of tooth loss, and presence of functional dentition among female heads of household under support of Welfare Organization in Mashhad, Iran. Materials and methods. In current study 556 participants aged 16-76 years were recruited. Sociodemographic character-istics (age, level of education, family size, and monthly income) were collected using interviewer-led questionnaire. Data about number of teeth and functional dentition were obtained by oral examination. The data were analyzed using Chi-square, Kruskal-Wallis, T-test and binary logistic regression analysis. Results. Four percent of participants were edentulous. Tooth loss was significantly associated with level of education, age and family size (P < 0.001). There was no significant association between level of income and tooth loss (P = 0.88). Only 37.5% of dentate subjects had functional dentition (anterior and premolar teeth). Women older than 40 years were 0.63 times less likely to have functional dentition than those younger than 40 years. Females with at least a high-school diploma were six times more likely to have functional dentition than their illiterate counterparts. Conclusion. Social determinants of functional dentition should be taken into account when planning oral health promoting programs for female heads of household. For reducing oral health inequalities access to dental services should be facilitated.